Od humanizmu ekologicznego i ekofilozofii do ekoteologii. Krytyka koncepcji duchowości ekologicznej H. Skolimowskiego - Rafał Czekalski (Studia Ecologiae et Bioethicae)
The purpose of this article was a review of the concept of ecological spirituality. Prior to this, however, the development of ecophilosophical thought of prof. Skolimowski has been presented. The starting point for Skolimowski’s philosophical thought is the holistic picture of the world (cosmology), which becomes the basis for the formulation of new ethics whose main attitude is reverence for the world and the man immersed in it. It is undoubtedly an original idea, opposing the canons and the paradigms valid in modern science. Skolimowski offers a holistic view of our civilization, the restoration of lost values, and inhibition of unilateral, i.e. materialistic progress. It is amazing how multifaceted Skolimowski’s publications are, ranging from strictly philosophical texts, regarding for instance analytical philosophy, to works concerning religious or social issues. The review of Skolimowski’s eco-theology has been conducted from the perspective of Catholic theology. The concept of God, spirituality, and the random treatment of other religions presented by Skolimowski are unacceptable. In reality, it is an attempt to subordinate religion to the assumptions of his own ecophilosophy.